Service Learning in the University: an experience within the framework of a subject of the Degree in Primary Education - Iván López-Fernández; Javier Benítez-Porres (Red U, 2018)
Bridging the connections between what students learn in the university and practice in real professional settings is a secular aspiration of higher education. Service learning is a methodology aimed at encouraging student learning through active participation in experiences related to community service. This methodology, although still testimonial, is growing in recent years in Spanish universities, highlighting initiatives of a voluntary nature for students and without a direct link to specific subjects. The present study describes an experience that incorporates service learning in a university subject framed in a curriculum for the training of teachers in Primary Education. A total of 67 university students, who gave lessons to 429 primary education students (aged 6-10), participated in the project. In order to record the opinion of the staff involved and the students’ perception of learning, several assessments tools were used, as questionnaires, interviews, journals and student reports were used. The results reflect the possibilities of service learning to reduce academic bias in curricula, increasing the relationships between theory and practice, and to enable students to acquire cross-curricular skills. Likewise, guidelines are provided that may be useful for any university teacher who aims to carry out this methodology with his students.